A high-sensitivity, fast-response and high-stability humidity sensor of curly flake Ti3C2Tx MXene prepared by electrolytic intercalation of NaOH solution. Issue 41 (10th October 2022) - Chen, Junji; Qin, Wenjing; Li, Kun; Feng, Lei; Chen, Jianxing; Qiao, Hanying; Yang, Min; Tian, Zhenhao; Li, Xinxin; Gu, Changshun; Wang, Yanli; Gong, Zheng; et al.
Abstract : A high-sensitivity humidity sensor based on curly flake Ti3 C2 T x MXene obtained by rapid NaOH electrolytic intercalation. Abstract : Ti3 C2 T x MXene has a high specific surface area and high conductivity, and can be used in the field of humidity sensing. By controlling the surface termination and microstructure of the material, it is expected to improve the humidity sensing performance of Ti3 C2 T x MXene. In this paper, we report a method of electrolytic intercalation treatment of Ti3 C2 T x MXene in NaOH solution. Theoretical and experimental results show that this method can remove the original F terminations from the surface of Ti3 C2 T x MXene and form a large number of OH and O terminations. The partial oxidation of the surface and the replacement of terminations and the insertion of Na + lead to the change of the Ti3 C2 T x MXene layer morphology from flat to curly and significantly improve the hydrophilicity and resistance. The curly flake structure constructs a fast channel for the entry and exit of water molecules which improves the hydration/dehydration efficiency of the material; the enhanced hydrophilicity of the material sharply reduces the resistance of the material after moisture absorption, which significantly improves the responsiveness of Ti3 C2 T x MXene to humidity. The curly flake Ti3 C2 T x MXene humidity sensor has an ultra-high sensitivity of S = 1.2 × 10 5 (two orders of magnitude higher than that of the reported humidity sensor based on MXene), with a fast response rate (2 s), good repeatability and stability (4 weeks), and it can be used for the analysis of human respiration rate, and also for non-contact sensing detection of the human body and environmental humidity detection.